Gordon, Ed., African American Women And The Vote, 1837-1965 - Ezell, David (Teaching History: A Journal of Methods, 1998)
African American Women and the Vote, 1837-1965 is a fine collection of essays dealing with a rarely documented topic: the struggle of African American women to assert themselves in American politics. It is always a pleasure to find a series of readable academic essays, and this book falls into that select group. It is a collection that offers both instructors and students several fine pieces for study and discussion.